PENGARUH PERKEMBANGAN BISNIS E-COMMERCE DAN SISTEM INFORMASI AKUNTANSI BERBASIS TEKNOLOGI TERHADAP KEBUTUHAN JASA AUDIT E-COMMERCE - Rizkia, Amara Suci; Feriyanto, Oon (Universitas Muhammadiyah Bengkulu, 2024)
This study aims to examine the impact of e-commerce business growth and technology-based accounting information systems on the demand for e-commerce audit services in Bandung. Using a descriptive quantitative approach, data was collected via questionnaires from a sample of 135 auditors at 13 public accounting firms. The sample consisted of 96 auditors selected through purposive sampling. Data were analyzed using multiple regression. Results indicate that the growth of e-commerce business does not significantly affect the demand for e-commerce audit services, with a significance level of 0.185, which is above 0.05. In contrast, technology-based accounting information systems significantly impact audit service needs, with a significance level of 0.000. Both factors simultaneously influence the demand for e-commerce audit services. Keywords: E-Commerce Business, E-Commerce, Accounting Information Systems, And E-Commerce Audit.